Is the more psychopathic more concerned with human beings overall? A data reanalysis exploration - Liu, Chuanjun; Liao, Jiangqun (Current psychology (New Brunswick, N.J.), 2023)
Previous research has found that those who are more psychopathic are more supportive of the actions that harm others to maximize the outcomes. This might be because the more psychopathic: 1) care more about the consequences; 2) care less about the “no harm” norms; 3) prefer action more often than inaction irrespective of consequences and norms. These possibilities are claimed to be dissociated by the so-called CNI model. We aimed to address the limitations of the CNI model by using an alternative algorithm that algebraically generates the probabilities of consequence sensitivity, norm sensitivity, and overall action bias ; the CAN algorithm for short. We applied the CAN algorithm and reanalyzed the raw data from four previous studies. The results demonstrated some new findings. People who are more psychopathic have more overall action bias, have stronger inaction and action preferences opposite to the requirements of norms and consequences, and have weaker inclinations to follow moral principles. Perceived societal standards, rather than personal standards, can alleviate the positive effects of psychopathy on overall action bias and action preference opposite to norms and consequences. The present study clarified and deepened our insights into the relationship between psychopathy and moral decisions. Theoretical and methodological implications are discussed.